Identification of potential quality markers of Zishen Yutai pill based on spectrum–effect relationship analysis - Wu, Sijia; Huang, Qiuling; Sheng, Feiya; Zhang, Lele; Zou, Liang; Yang, Lele; Cao, Jiliang; Pang, Xiufei; Ning, Na; Li, Peng (Frontiers in Pharmacology, 2023)
The current quality evaluation of traditional Chinese medicine (TCM) is hard to attribute with clinical efficacy due to the complexity of TCM. Zishen Yutai Pill (ZYP), a well-known traditional Chinese patent medicine, has been widely used to prevent recurrent miscarriage and treat threatened abortion. However, the chemical components of ZYP are unknown and there is no convincing quality control method applied on ZYP. Although ZYP has been found to promote endometrial receptivity and treat impending abortion, the substantial basis of the therapeutic effects is unclear. The aim of this study was to clarify the quality markers correlated to the potential medicinal activities and provide a theoretical foundation for scientific quality control and product quality improvement of ZYP. The chemical constituents of ZYP were comprehensively analyzed by offline two-dimensional liquid chromatography-mass spectrometry (2DLC-LTQ-Orbitrap-MS). The efficacy of the 27 ZYP orthogonal groups was investigated using HTR-8/SVneo oxidative damage model and migration model in vitro, as well as endometrial receptivity disorder mouse model and premature ovarian failure mouse model in vivo. Based on the efficacy and mass spectral results, spectrum-effect relationship analysis was used to identify the chemical components with corresponding pharmacological activities. A total of 589 chemical components were found in ZYP, of which 139 were not identified in the literature. The potential quality markers for ZYP were successfully identified through orthogonal design and spectrum-effect relationship analysis. By combining mass spectrum data and pharmacological results of 27 orthogonal groups, 39 substances were identified as potential quality markers. The approaches used in this study will provide a feasible strategy for discovery of quality markers with bioactivity and further investigation on the quality evaluation of TCM.